Ab-initio Calculations of the Structural, Electronic and Optical Properties of (CdSe)2 Clusters - Alselawe A.I.A.; Jumali M.H.H.; Gopir G.; Anas M.M. (Penerbit Universiti Kebangsaan Malaysia, 2024)
Indexed by WOS/SCOPUS/ERA